(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2023)
Background: Peritoneal tuberculosis is a rare form of extrapulmonary tuberculosis, which can result from the reactivation of latent foci in the peritoneal cavity. Case presentation: A 19-year-old female presented to the gynecological oncology clinic with a two-month history of generalized abdominal pain and progressive abdominal distention. An abdominopelvic computed tomography scan revealed a cystic right adnexal lesion with massive simple ascites. A frozen abdomen was noted during exploratory laparotomy. Histological examination of the peritoneal biopsy reported granulomatous nodules with numerous epithelioid histiocytes. Postoperatively, she was managed with rifampicin, isoniazid, pyrazinamide, ethambutol, and pyridoxine for six months and recovered fully. Conclusion: Peritoneal tuberculosis may mimic ovarian and peritoneal malignancies. A high suspicion index of peritoneal tuberculosis should be entertained in patients presenting with nonspecific symptoms of ovarian or peritoneal cancers.